2012
DOI: 10.1371/journal.pone.0036137
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Distributions of NUP62 and NUP214 Suggest Architectural Diversity and Spatial Patterning among Nuclear Pore Complexes

Abstract: The shape of nuclei in many adherent cultured cells approximates an oblate ellipsoid, with contralateral flattened surfaces facing the culture plate or the medium. Observations of cultured cell nuclei from orthogonal perspectives revealed that nucleoporin p62 (NUP62) and nucleoporin 214 (NUP214) are differentially distributed between nuclear pore complexes on the flattened surfaces and peripheral rim of the nucleus. High resolution stimulated emission depletion (STED) immunofluorescence microscopy resolved ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…While SIM provides for increased resolution in detecting individual spots within isolated nuclei, it remains an open question as to whether this represents a singular or multiple Nup molecules within an NPC for each spot detected. Interestingly, there have been reports that the composition of each NPC within a single nucleus in a given cell can vary as individual nucleoporins are replaced and also varies amongst cell types (Kinoshita et al, 2012;Rajoo et al, 2018;Toyama et al, 2018). Given that little is known about the human neuronal nuclear pore complex, NPC heterogeneity within individual nuclei which may explain differences in Nup staining patterns.…”
Section: Discussionmentioning
confidence: 99%
“…While SIM provides for increased resolution in detecting individual spots within isolated nuclei, it remains an open question as to whether this represents a singular or multiple Nup molecules within an NPC for each spot detected. Interestingly, there have been reports that the composition of each NPC within a single nucleus in a given cell can vary as individual nucleoporins are replaced and also varies amongst cell types (Kinoshita et al, 2012;Rajoo et al, 2018;Toyama et al, 2018). Given that little is known about the human neuronal nuclear pore complex, NPC heterogeneity within individual nuclei which may explain differences in Nup staining patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We do not completely exclude the possibility that the mitotic defects (cell cycle arrest, multiple nuclei, spindle mis-orientation, and supernumerary centrosomes) were also related to the role of Nup62 during interphase. We imagine that the concentration of Nup62 could influence sensitivity to centrosome synthesis and segregation during interphase; however, reduction of nucleocytoplasmic transport mediated by Nup62 does not appear to be part of this mechanism 37 , 41 . It is very difficult to imagine that Nup62 is solely responsible for trafficking the majority of centrosome components (>100 proteins) or those proteins responsible for cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the existence of different NPCs in the same nucleus, it has been observed that yeast NPCs adjacent to the nucleolus lack Mlp proteins, but those away from the nucleolus still contain these proteins 161 . In addition, a differential distribution of NUP62 and NUP214 among different NPCs was recently proposed in mammalian cells 162 , and high-resolution imaging of mRNA nuclear export indicates that not all NPCs are equally active and that mRNA molecules scan several pores before being shuttled into the cytoplasm 38 . Although these findings could suggest the presence of NPCs that are specialized in mRNA export, they could also be indicative of inactive or transport saturated NPCs rather than pores with different functions.…”
Section: Final Perspectivementioning
confidence: 99%